2018
DOI: 10.1007/978-3-319-74098-0_8
|View full text |Cite
|
Sign up to set email alerts
|

Transparency in Health Care: Disclosing Adverse Events to the Public

Abstract: The topic of transparency has received increasing academic interest in recent years. Transparency can be interpreted as conducting affairs in the open, being subject to public scrutiny, or admitting to problems when they arise. This chapter analyses transparency in disclosing adverse events to the public in Norway. We use the widely publicized Daniel case to show the communication between the regulator and the public, discussing key elements of transparency in the healthcare setting, including the role of medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

5
1

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
0
12
0
2
Order By: Relevance
“…To date, we have lacked knowledge about next of kin’s involvement in such regulatory investigations. Informing investigations of adverse events causing death by involving next of kin is innovative regulation-wise, 20 , 23 and it is important to map and learn from next of kin’s experiences. Similar to other studies, 1 , 12 , 13 we found that next of kin had different conceptualizations of the event compared with what was presented in the written information.…”
Section: Discussionmentioning
confidence: 99%
“…To date, we have lacked knowledge about next of kin’s involvement in such regulatory investigations. Informing investigations of adverse events causing death by involving next of kin is innovative regulation-wise, 20 , 23 and it is important to map and learn from next of kin’s experiences. Similar to other studies, 1 , 12 , 13 we found that next of kin had different conceptualizations of the event compared with what was presented in the written information.…”
Section: Discussionmentioning
confidence: 99%
“…For example, this framing of situated, structural and systemic resilience can provide a framework for focusing attention on the critical questions of how, when and why fluctuations become disruptions, and how disruptions expand in scale to provoke larger moments of resilience that increasingly enroll greater numbers of stakeholders across a system and ultimately challenge, reorganize and reform core elements of that system. To take one practical example from healthcare: media reports and public pressure relating to the handling of a harmful adverse event can act as a significant disruption for a regulatory body, prompting a rapid response to review and reopen an investigation using existing organisational resources and models (situated resilience); which in turn can provoke the design and reorganization of new processes for involving next-of-kin and outside experts in inquiries (structural resilience); and ultimately can lead to system-wide recommendations for reforming the underling mechanisms of collaboration between regulatory bodies involved in assessing compliance with core regulatory requirements (systemic resilience) [3]. This example illustrates how an integrative framework for resilience should be flexible enough to accommodate granular details related to a single organization and event, whilst also providing a language to explain the 'scaling up' of resilience across entire systems and over long time periods.…”
Section: Towards An Integrative Framework Of Resiliencementioning
confidence: 99%
“…Det har i flere år blitt rettet kritikk mot at pasienter, brukere og pårørende har hatt for liten involvering i tilsynsaktiviteter generelt og i oppfølging av alvorlige hendelser i helsetjenesten spesielt [1][2][3][4][5][6][7]. En overordnet målsetting fra tilsynsmyndighetene er derfor å styrke involvering av etterlatte i tilsynssaker samt å ta i bruk de etterlatte og pårørende sine erfaringer som en ressurs for å utvikle brukerperspektivet i norsk tilsynspraksis [5,8].…”
Section: Bakgrunnunclassified
“…Dette kan dreie seg om intervjuer eller møter med involverte parter i motsetning til kunnskapsinnhenting som i hovedsak baserer seg på gjennomgang av journalnotater, dokumenter og skriftlige uttalelser.Slike møter med involverte parter kan bidra til mer effektive laeringsprosesser og bør i større grad utforskes med tanke på videre metodeutvikling i konteksten av tilsynsmyndighetens mandat og aktiviteter[18,19]. Sentralt for å få dette realisert er en sterk ledelsesforankring og videre utvikling av seleksjonskriterier knyttet til hvilke type saker som egner seg for en mer direkte dialog med involverte parter i de ulike tilsynssakene.Frem til nå har det vaert manglende kunnskap om hva etterlatte sin involvering i tilsyn kan bidra til, og tiltaket dette prosjektet representerer er i så måte innovativ[7,20]. Innovasjon i tilsynsmetoder for å innhente et godt kunnskapsgrunnlag for vurdering av tilsynssaker er i stadig utvikling, og i den senere tid har brukerinvolvering stått sentralt nasjonalt og internasjonalt[11,12,24].…”
unclassified